Pipeline Embolization Device for Small and Medium Vertebral Artery Aneurysms: A Multicenter Study. Issue 5 (29th May 2023) - Zhang, Hongyun; Zhang, Hongqi; Liu, Jianmin; Song, Donglei; Zhao, Yuanli; Guan, Sheng; Maimaitili, Aisha; Wang, Yunyan; Feng, Wenfeng; Wang, Yang; Wan, Jieqing; Mao, Guohua; et al.
Abstract : BACKGROUND: Pipeline embolization devices (PEDs) have been increasingly used for the treatment of posterior circulation aneurysms. OBJECTIVE: To investigate the safety and efficacy of PED in the treatment of small to medium unruptured vertebral artery intracranial aneurysms (VAIAs). METHODS: Data from 76 patients with 78 unruptured small and medium (≤12 mm) VAIAs were analyzed. Data for this study come from the PLUS study, which was conducted at 14 centers in China from 2014 to 2019. Univariate analyses were performed to evaluate predictors of the occlusion and complication. RESULTS: Seventy-eight aneurysms in 76 patients were treated with PED. The mean aneurysm size was 8.28 ± 2.13 mm, and all PEDs were successfully placed. The median follow-up was 7 months and available for 67 (85.9%) aneurysms. Complete occlusion was seen in 60 (89.6%) aneurysms, which 86.6% met the primary efficacy outcome. All patients received clinical follow-up, the combined major morbidity and mortality was 2.6%, and 98.7% of patients had a good prognosis. Ischemic stroke occurred in 10.5% of patients, and adjuvant coil and successful after adjustment were predictors of ischemic stroke in the early postoperative and follow-up, respectively. There was no significant difference in the occlusion rate of aneurysm involving posterior inferior cerebellar artery ( P = .78). In cases where posterior inferior cerebellar artery was covered by PED, there was no significant difference in ischemic stroke. CONCLUSION: In the treatment of unruptured ≤12 mm VAIAs, PED has a high surgical success rate, a high degree of occlusion, and low morbidity and mortality. PED may be a promising endovascular technique.